If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 30 + -1x = 5x + 6 Reorder the terms: 30 + -1x = 6 + 5x Solving 30 + -1x = 6 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 30 + -1x + -5x = 6 + 5x + -5x Combine like terms: -1x + -5x = -6x 30 + -6x = 6 + 5x + -5x Combine like terms: 5x + -5x = 0 30 + -6x = 6 + 0 30 + -6x = 6 Add '-30' to each side of the equation. 30 + -30 + -6x = 6 + -30 Combine like terms: 30 + -30 = 0 0 + -6x = 6 + -30 -6x = 6 + -30 Combine like terms: 6 + -30 = -24 -6x = -24 Divide each side by '-6'. x = 4 Simplifying x = 4
| -43+x=23-2x | | 33.6=H^(3/2) | | 2w+10=48 | | 6x+2(5x-5)=8-3(2x+1) | | 60=256-x | | 5.9h+2.15=20 | | 3x+23+7x-37=180 | | 1-4cosx=-3 | | 73=-6g+97 | | 33.6=H^3/2 | | 8p=97 | | j+23=3 | | 12=6a+2 | | 3x+7y+23=30 | | m=(h-w)/8 | | 7=6c+1 | | 3+4(t+2)=2t-2 | | -y+244=179 | | j+23=-s | | 11+4x+2+3x=90 | | P-3+8=8 | | 0.5(3z+7)+17.7=0.7(3z-4) | | -0.72m=-2 | | 73=9h+1 | | A+B=4X-2 | | 14-3p+1=4+p | | 3.33=-.5 | | 185=35-x | | 750+0.2=1050 | | A+B=4X-8 | | (5.3x+8.2y)+(13.3y-4.1x)= | | 0=8n+7n |